The determination of 210Pb in the sediments: sedimentation rates from the Terengganu coastal waters, Malaysia - Yunus, Kamaruzzaman; Ong, Meng Chuan (Oriental Scientific Publishing Company, 2010)
Detail 210Pb analysis of two core samples collected with a gravity corer from the coastal water of Terengganu South China Sea has provided a chronology of the sediments identifying the subtle yet distinct variations in recent sedimentation. This investigation of recent sedimentation with the use of 210Pb analyses is a part of an overall study to examine and quantify past and present patterns and rates of sedimentation, revealing how deposition environments and their morphological structure transform. To assess the recent to sub-recent depositional processes in the Terengganu coastal water, a detailed sediment analysis was conducted. The activities of natural radionuclide 210Pb along with the 208Po tracer were measured by Alpha Spectrometry to estimate sedimentation rate and mass accumulation rate. The highest accumulation rates were recorded near the Terengganu river estuary, seem to be controlled by several addition factors that modulate the settling particles, such as onshore precipitation and river runoff and the lower rates near the island.